Nisbah N/K jerami dan hasil tiga varietas padi (oryza sativa L.) pada pemberian hara N, P dan K alternatif berbasis teknologi eksisting petani - Yustisia Yustisia; Tohari Tohari; Dja’far Shiddieq; Subowo Subowo (Jurnal Ilmu Tanah dan Air, 2017)
The most farmers in the lowland use N, P and K nutrients from urea, SP 36 and KCl fertilizer severally. The combined rates of NPK, NK, PK and NP was given varies by farmers. Its expected that N/K ratio of straw and grain yield varies with varieties and varies with NPK, NK, PK and NP combined rates. Pot experiment aimed to identify N/K ratio of straw and grain yield and test the several combined rates of N, P and K nutrients and its effectiveness based on the farmers’s technology. The experiment was conducted in Glasshouse of Agriculture Faculty, Gadjah Mada University during dry season 2009. The experiment applied Randomized Split Plot Design and each treatment was repeated 3 times. The Main Plot treatment consisted of 3 rice varieties: IR 64, Ciherang and Cimelati. The Sub Plot treatment consisted of 5 combined doses of N, P and K based on the farmers’s technology as a reference (+NPK): 222.26 kg ha-1 N, 56.80 kg ha-1 P2O5 and 47.67 kg ha-1 K2O; (0 NPK); (0 N + PK); (0 P + NK); and (0 K + NP). The result showed that the highest straw N/K ratio was achieved by IR 64. It was significantly different with Ciherang and Cimelati. The grain yield of IR 64, Ciherang and Cimelati was not significantly different. Considering its grain yield, Ciherang and Cimelati can be used as alternative of variety for farmers. The highest grain yield (77,089 g.pot-1) and highest RAE value (107,68%) was achieved by (0 P + NK) treatment. The RAE value in (0 P + NK) treatment was achieved by Ciherang (121.74%) and IR 64 (117.07%). The lowest of grain yield was achieved by (0 NPK) and (0 N + PK) treatments. It was affected by an imbalance of straw N/K ratio due to the effect of Inceptisol’s native soil properties (low N, high P and K). Based on the grain yield and RAE value, combined rate of 0 P + NK (0 kg P2O5/ha, 222.26 kg N/ha and 47.67 kg K2O/ha) can be used as alternative of N, P, K fertilization.